ANALISIS PERMASALAHAN PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 DITINJAU DARI PEMAHAMAN KONSEP MATEMATIKA SISWA SMK - Nailul Himmi; Nina Agustyaningrum; Iswanti Iswanti (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Online learning is carried out to prevent the widespread spread of COVID-19 cases.The study was conducted to determine the online learning process during the COVID-19 pandemic in terms of understanding the mathematical concepts of SMK students in Sagulung District. The research method is descriptive qualitative. The research subjects were 172 SMK students in Sagulung District. Purposive sampling technique is a technique of taking research subjects. The instrument used valid and reliable tests and questionnaires in the form of tests (r = 0.74) and questionnaires (r = 0.83). The analysis technique is in the form of data collection, data reduction, presenting data and drawing conclusions. The results showed that the online learning problems experienced by students in terms of the three categories of ability to understand mathematical concepts had similarities, namely the indicators of information technology-based learning resources, learning duration, and students' learning independence. So from these findings it can be suggested to educators that in online learning to make more use of information technology, maximize the duration of learning and increase the learning independence of students.